Students’ Problems In Pronouncing -Ed Endings In Reading Aloud At Universitas Pgri Sumatera Barat - Ikhsan, Muhammad Khairin (JUPE : Jurnal Pendidikan Mandala, 2023)
This research is aimed at analyzing students’ problems in pronouncing -ed endings in reading aloud at Universitas PGRI Sumatera Barat registered in 2022/2023 academic year. This research was conducted since there were lots of students got difficulties in pronouncing -ed endings in the classroom activities. In addition, the research method used by the reseracher was qualitative descriptive. However, the instruments used were reading aloud test, interview, and audio recording. The researcher took 42 students as the sample to be tested. After conducting the test, the researcher got 30 students who got a low score, and the were interviewed as the sample of this research. The findings of this research showed that most problems occurred were caused by the difference between the way to pronounce the words of their mother tongue and English, locality (environment), personality, motivation, and lack of knowledge.